The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
1988
DOI: 10.1159/000266751
|View full text |Cite
|
Sign up to set email alerts
|

Aqueous Humor Flow Rate and Intraocular Pressure during and after Pregnancy

Abstract: Intraocular pressure and aqueous humor formation rate have been determined from the first trimester of pregnancy through term, with further determinations 3 months postpartum, in 7 patients. The intraocular pressure showed a consistent, statistically significant fall during pregnancy, returning to values seen in early pregnancy after delivery. Aqueous humor formation rate showed no change during pregnancy. The data indicate that the sustained elevated hormonal levels during pregnancy, either directly or indire… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
33
0
2

Year Published

1994
1994
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 56 publications
(40 citation statements)
references
References 11 publications
5
33
0
2
Order By: Relevance
“…10,11 Moreover, it has been reported that physiologic changes during pregnancy (especially in late pregnancy) lead to a mild decrease in the IOP compared to the pressure before pregnancy. [12][13][14][15][16][17][18] This change obviates using multiple classes of antiglaucoma medications to control IOP. After delivery, the oral carbonic anhydrase inhibitors were replaced by topical carbonic anhydrase inhibitors and latanoprost in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…10,11 Moreover, it has been reported that physiologic changes during pregnancy (especially in late pregnancy) lead to a mild decrease in the IOP compared to the pressure before pregnancy. [12][13][14][15][16][17][18] This change obviates using multiple classes of antiglaucoma medications to control IOP. After delivery, the oral carbonic anhydrase inhibitors were replaced by topical carbonic anhydrase inhibitors and latanoprost in all patients.…”
Section: Methodsmentioning
confidence: 99%
“…In the literature, there is an evidence for a direct effect of endogenous hormonal changes on aqueous humor circulation. [12,13,14,15] Population based studies have shown that IOP is equal between the sexes in ages of 20 to 40 yrs .In older age group, an increase in mean IOP with age is greater in females than males. The use of hormone replacement therapy and the protective effect of endogenous hormones could explain the gender difference.…”
Section: Discussionmentioning
confidence: 99%
“…The increased levels of estrogen, progesterone and other placental hormones during pregnancy may play an important role in maintaining the IOP. 1,[6][7][8] IOP may affect women of childbearing age. A decrease in intraocular pressure has been observed during pregnancy and often persists for few months after delivery.…”
Section: Discussionmentioning
confidence: 99%
“…This result in a gradual, statistically significant fall of the IOP during pregnancy. [6][7][8][9] Progesterone has glucocorticoid antagonistic properties and this antagonistic action helps in the lowering of the IOP. The changes in the aqueous dynamics are consistent with the hypothesis that excess progesterone, during pregnancy, blocks the ocular hypertensive effect of endogenous corticosteroids.…”
Section: Discussionmentioning
confidence: 99%